Places for people : hotels, motels, restaurants, bars, clubs, community recreation facilities, camps, parks, plazas, playgrounds : examples of outstanding achievement - Davern, Jeanne M.;White, Jan V. (New York : McGraw Hill Education, 1976)
The new book offers impressive affirmation of the belief expressed in the introduction to the earlier volume that "the case for competent design will become better understood as competition increases".
Preface -- Index -- Part I. Places to stay: 1. The new "grand hotels" -- 2. The new "small hotels" -- 3. Resort hotels/on the water -- 4. Resort hotels/in snow country -- 5. Lodges that invite conferences -- Part II. Places to eat, drink, enjoy!: -- 1. Restaurants and bars -- 2. Clubs -- Part III. Places to play: 1. Community recreation facilities -- 2. Camps -- 3. Parks, plazas and playgrounds -- 4. The 50th state: "Test for the landscape fo tourism.".
Includes index.
Keywords: HOTELS